Islamiyat (a core text for cambridge olevel) - Thomas, David (Oxford University Press; Karachi, 2011)
"Islamiyat (A Core Text for Cambridge O-Level)" provides a comprehensive study of Islamic history, teachings, and ethical principles, preparing students for a deeper understanding of Islam in the context of their O-Level examinations.